The Long-lasting Shadow of the Allied Occupation of Austria on its Spatial Equilibrium - Christoph Eder; Martin Halla (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
After World War II, Austria was divided into four occupation zones for 10 years. We exploit the migration shock out of the Soviet zone to understand why economic activity is distributed unevenly in space. We show that the distorted population distribution has fully persisted until now. More direct measures of economic activity show an even higher concentration in the former non-Soviet zone. This gap in economic activity is growing over time, mainly due to commuting out of the former Soviet zone.
Keywords: R12; 330